2‐Furanylboronic Acid as an Effective Catalyst for the Direct Amidation of Carboxylic Acids at Room Temperature. Issue 5 (8th January 2015) - Tam, Eric Kwok Wai; Rita,; Liu, Lionel Yiqian; Chen, Anqi
Abstract: 2‐Furanylboronic acid has been identified as an inexpensive and effective catalyst for the dehydrative amide formation of carboxylic acids and amines. This transformation can be efficiently carried out at room temperature and is applicable to a wide range of carboxylic acids with primary and secondary amines to afford amides in good to excellent yields. Abstract : Commercially available, inexpensive 2‐furanylboronic acid has been identified as an effective catalyst for the direct dehydrative amide formation of carboxylic acids and amines. This transformation can be efficiently carried out at room temperature and is applicable to a wide range of carboxylic acids with primary and secondary amines to afford amides in good to excellent yields.